High power laser powder bed fusion of Ti6Al4V alloy: The control of defects, microstructure, and mechanical properties - Jinfeng Deng; Qiao Zhong; Jia Chen; Kaiwen Wei; Xiaoze Yue; Yuguang Liu; Gaohang Li; Xiangyou Li; Xiaoyan Zeng (Journal of Materials Research and Technology)
Laser powder bed fusion (LPBF) is the most widely used metal additive manufacturing technology, but it still faces challenges in manufacturing efficiency. To address the issue, high-power LPBF (HP-LPBF) which employs kilowatt-level lasers emerges in recent years. In this study, a 4 kW Flat-top laser was used for the HP-LPBF of Ti6Al4V alloy. The samples in as-built state and annealed states (750 °C/2h, 850 °C/2h, 950 °C/2h, 1050 °C/2h) were investigated in terms of defects, microstructure, and mechanical properties. Results show that keyhole mode melting is avoided by adopting the Flat-top laser, so the relative density of as-built Ti6Al4V is generally positively correlated with the employed laser energy density. The minimum laser energy density to obtain the high-density (≥99.9%) sample is 50.0 J/mm3, and the highest build rate is 288 cm3/h. The microstructure in as-built state exhibits a unique alternating pattern of ''bright bands/dark bands''. The dark bands consist of needle-shaped α′ martensite, while the bright bands consist of needle-shaped α+β, which results from the decomposition of α′ under the in-situ annealing effect of the 4 kW Flat-top laser. After annealing at 750 °C, most of the residual α′ decomposes into needle-shaped α+β. As the annealing temperature increases from 750 °C to 1050 °C, the microstructure undergoes an evolution from needle-shaped α+β to lamellar α+β then to lamellar α+β with some globular α and finally to duplex α+β. An optimum strength-ductility balance is achieved after annealing at 850 °C, both the tensile strength and the elongation exceed the standard values of Ti6Al4V forgings.